The Comfortable Home and Energy Consumption. Issue 3 (3rd July 2018) - Madsen, Line Valdorff
Abstract: This paper investigates relations between notions of comfort and notions of home, aiming at a better understanding of residential comfort and the related energy consumption. Residential comfort is examined through a practice-theoretical lens and as something that appears in between the social and material structures of a home. The approach considers different elements of comfort in homemaking practices, such as the body, materials and social meanings. The paper examines how conceptions of comfort and homeliness interrelate through homemaking practices and thereby redefine comfort within a framework of the home and social practices. This implies focus on "the comfortable home" as made up of homemaking practices that include knowhow, sensations and social norms. The empirical basis comprises interviews and visual data from a field study on detached housing on the outskirts of a Danish city. The paper concludes that the notion of home is central in understanding comfort and energy consumption in dwellings, as conceptions of comfort and home are intertwined but also carry different meanings. The different rooms of a house relate differently to the notions of home and comfort, which has implications for how energy is consumed within the home.